2018
DOI: 10.7150/jca.25213
|View full text |Cite
|
Sign up to set email alerts
|

Cry 1 Regulates the Clock Gene Network and Promotes Proliferation and Migration Via the Akt/P53/P21 Pathway in Human Osteosarcoma Cells

Abstract: The many circadian clock genes buildup a network structure that controls physiological processes such as sleep cycle, metabolism and hormone secretion. A close relationship exists between circadian rhythm and cancers because cell cycle is affected by clock controlled genes (CCGs), including Cyclin D1, Cyclin A, Cyclin E and P21. The abnormal expression of the core circadian clock gene Cryptochrome 1 (Cry1) was found in many types of cancers. However, it is still unclear the exact mechanism of Cry1 dysregulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…Moreover, in some tumors, BHLHE40 appears to have a bimodal function -it is upregulated during tumor initiation, whereas its expression is lost during tumor progression, exhibiting a significant decrease in expression from well-differentiated to poorly differentiated tumors. BHLHE40 is primarily a transcriptional regulator [28,61,37] that is often deleted or downregulated in cancer, including Burkitt's lymphoma [62], osteosarcoma [63], non-small cell lung cancer [64] and in pancreatic cancer [65]. Paradoxically, BHLHE40 is also upregulated in many cancers, such as in gastric cancer [66,67] and in breast cancer [68].…”
Section: Expression Of Bhlhe40 In Cancermentioning
confidence: 99%
“…Moreover, in some tumors, BHLHE40 appears to have a bimodal function -it is upregulated during tumor initiation, whereas its expression is lost during tumor progression, exhibiting a significant decrease in expression from well-differentiated to poorly differentiated tumors. BHLHE40 is primarily a transcriptional regulator [28,61,37] that is often deleted or downregulated in cancer, including Burkitt's lymphoma [62], osteosarcoma [63], non-small cell lung cancer [64] and in pancreatic cancer [65]. Paradoxically, BHLHE40 is also upregulated in many cancers, such as in gastric cancer [66,67] and in breast cancer [68].…”
Section: Expression Of Bhlhe40 In Cancermentioning
confidence: 99%
“…The results of GSEA with c2.cp.kegg.v7.0.symbols.gmt as the reference gene set showed that the enrichment pathways were mainly involved in the circadian rhythm, oxidative phosphorylation, DNA replication and ECM-receptor interaction pathway. Previous reports have shown that oxidative phosphorylation [39,40], circadian rhythm [41], and DNA replication [42] were closely related to the occurrence and progress of OS. Another study has reported that ECM-receptor interaction pathway plays an important role in the occurrence, development, invasion and metastasis of malignant tumors [43].…”
Section: Discussionmentioning
confidence: 94%
“…Downregulation of circadian clock genes in cancer cells has also been correlated with increased cell migration and invasion. Studies have shown that inhibition of CRY1 , PER2 or BMAL1 results in enhanced cell migration or invasion via the Akt signalling pathway, in osteosarcoma ( CRY1 and PER2 ) and lung cancer and glioma cells ( BMAL1 ). In addition, BMAL1 knockout, resulting in loss of circadian rhythmicity, results in increased invasion of breast cancer cells .…”
Section: The Circadian Clock Influences Epithelial‐to‐mesenchymal Tramentioning
confidence: 99%